2016
DOI: 10.1155/2016/1548326
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Infectious Agents and Other Pollutants in Automobiles for Domestic Use: Potential Health Impacts and Approaches to Risk Mitigation

Abstract: The world total of passenger cars is expected to go from the current one billion to >2.5 billion by 2050. Cars for domestic use account for ~74% of the world's yearly production of motorized vehicles. In North America, ~80% of the commuters use their own car with another 5.6% travelling as passengers. With the current life-expectancy of 78.6 years, the average North American spends 4.3 years driving a car! This equates to driving 101 minutes/day with a lifetime driving distance of nearly 1.3 million km inside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Similarly, the dust generated in the streets, especially of Kathmandu Valley is also considered to be equally responsible for the microbial colonization (Gautam 2010;Sattar 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the dust generated in the streets, especially of Kathmandu Valley is also considered to be equally responsible for the microbial colonization (Gautam 2010;Sattar 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Inhalation of such particulates, including those from tobacco smoke (33), and their retention in the respiratory system can predispose to many pathogens. In-car exposure to such partic-ulates (34) and volatile organic compounds (VOCs) (35) may occur simultaneously, potentially leading to an additive negative impact on the health of the occupants (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Ill-functioning ventilation or air-conditioning systems in various institutions, dwellings and personal cars, could also be a cause of the inhalable air contamination and subsequent respiratory disease [22,103,104,105]. Kumar and Morawska [104] reported that an ill-regulated air-conditioning (A/C) system set on indoor recirculation mode, caused local outbreaks of COVID-19 in a bus and in conference rooms.…”
Section: Prevention Of Dampness and Air Contamination By Illfunctionimentioning
confidence: 99%
“…Sattar et al [105] reported that biofilms formed in heaters/ air conditioners of personal cars, as well as those in windshield washer reservoirs and other areas of the car, may release infectious microorganisms such as Legionella pneumophila, allergenic ones such as nontuberculous mycobacteria, causing HP, and immunotoxic microbial products such as bacterial endotoxin and/or fungal (1→3)-β-D-glucan.…”
Section: Prevention Of Dampness and Air Contamination By Illfunctionimentioning
confidence: 99%